MAYBE Initial complexity problem: 1: T: (1, 1) f0(a) -> f1(a) (?, 1) f1(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(a) with all transitions in problem 1, the following new transition is obtained: f0(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 ] We thus obtain the following problem: 2: T: (1, 2) f0(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 ] (?, 1) f1(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 ] with all transitions in problem 2, the following new transition is obtained: f0(a) -> f1(a) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] We thus obtain the following problem: 3: T: (1, 3) f0(a) -> f1(a) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] (?, 1) f1(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(a) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] with all transitions in problem 3, the following new transition is obtained: f0(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] We thus obtain the following problem: 4: T: (1, 4) f0(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] (?, 1) f1(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] with all transitions in problem 4, the following new transition is obtained: f0(a) -> f1(a) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] We thus obtain the following problem: 5: T: (1, 5) f0(a) -> f1(a) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] (?, 1) f1(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(a) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] with all transitions in problem 5, the following new transition is obtained: f0(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] We thus obtain the following problem: 6: T: (1, 6) f0(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] (?, 1) f1(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] with all transitions in problem 6, the following new transition is obtained: f0(a) -> f1(a) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] We thus obtain the following problem: 7: T: (1, 7) f0(a) -> f1(a) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] (?, 1) f1(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(a) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] with all transitions in problem 7, the following new transition is obtained: f0(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] We thus obtain the following problem: 8: T: (1, 8) f0(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] (?, 1) f1(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] with all transitions in problem 8, the following new transition is obtained: f0(a) -> f1(a) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] We thus obtain the following problem: 9: T: (1, 9) f0(a) -> f1(a) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] (?, 1) f1(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(a) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] with all transitions in problem 9, the following new transition is obtained: f0(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] We thus obtain the following problem: 10: T: (1, 10) f0(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] (?, 1) f1(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] with all transitions in problem 10, the following new transition is obtained: f0(a) -> f1(a) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] We thus obtain the following problem: 11: T: (1, 11) f0(a) -> f1(a) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] (?, 1) f1(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(a) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] with all transitions in problem 11, the following new transition is obtained: f0(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] We thus obtain the following problem: 12: T: (1, 12) f0(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] (?, 1) f1(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] with all transitions in problem 12, the following new transition is obtained: f0(a) -> f1(a) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] We thus obtain the following problem: 13: T: (1, 13) f0(a) -> f1(a) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] (?, 1) f1(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(a) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] with all transitions in problem 13, the following new transition is obtained: f0(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] We thus obtain the following problem: 14: T: (1, 14) f0(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] (?, 1) f1(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] with all transitions in problem 14, the following new transition is obtained: f0(a) -> f1(a) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] We thus obtain the following problem: 15: T: (1, 15) f0(a) -> f1(a) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] (?, 1) f1(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a) -> f1(a) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] with all transitions in problem 15, the following new transition is obtained: f0(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] We thus obtain the following problem: 16: T: (1, 16) f0(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 /\ 1 >= -a + 1 /\ -a + 1 >= 0 ] (?, 1) f1(a) -> f1(-a + 1) [ 1 >= a /\ a >= 0 ] start location: f0 leaf cost: 0 Complexity upper bound ? Time: 1.015 sec (SMT: 0.958 sec)